Sex and gender differentials in the prevalence of obesity and its association with multimorbidity among reproductive-aged individuals in India - Murmu, Jogesh; Sinha, Abhinav; Agrawal, Ritik; Rout, Bhagyashree; Kanungo, Srikanta; Pati, Sanghamitra (Frontiers in Public Health, 2025)
IntroductionThe increase in the prevalence of obesity has become a common public health issue worldwide, with low- and middle-income countries (LMICs) like India witnessing an equal rise. It makes a considerable contribution to chronic diseases as it is a major risk factor for other chronic illnesses. Multimorbidity, or the presence of two or more chronic illnesses, is becoming more common in LMICs, resulting in poor health outcomes. However, research on obesity and multimorbidity in younger populations in LMICs is scarce, with most studies focusing on older persons. The study analyzed sex differences in the prevalence of obesity among reproductive-aged persons and its association with multimorbidity, as well as investigated their health-seeking behaviors.MethodsData from the National Family Health Survey (NFHS-5) involving 751,831 females and 100,656 males were analyzed. Multimorbidity was defined by the presence of two or more chronic conditions out of the eight included chronic conditions. Multivariable logistic regression was applied to identify factors associated with obesity.ResultThe prevalence of obesity was 48.90% (95% CI: 48.60–49.20%) among males and 57.10% (95% CI: 57.00–57.22%) among females. Waist-to-Hip Ratio (WHR) revealed higher obesity rates in females with multiple chronic conditions (70.8%) compared to males (65.1%). Males with multimorbidity had a 47% higher likelihood of having obesity (AOR: 1.47, 95% CI: 1.13–1.89, p < 0.003) compared to individuals without obesity.ConclusionThe study highlights high obesity prevalence among reproductive-aged individuals in India, with females having higher obesity rates overall. However, males with multimorbidity exhibit a significantly greater likelihood of obesity than males without. These findings emphasize the need for gender-specific public health strategies addressing obesity and multimorbidity, including promoting healthier diets, increasing physical activity, and improving disease management for both women and men.